2021
DOI: 10.3390/jof8010008
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of Endophytic Actinobacteria against Fusarium solani, the Causal Agent of Sudden Decline Syndrome on Date Palm in the UAE

Abstract: Thirty-one endophytic streptomycete and non-streptomycete actinobacteria were isolated from healthy date palm root tissues. In vitro screening revealed that the antifungal action of isolate #16 was associated with the production of cell-wall degrading enzymes, whereas with diffusible antifungal metabolites in isolate #28, albeit their production of volatile antifungal compounds. According to the 16S rRNA gene sequencing, isolates #16 and #28 were identified as Streptomyces polychromogenes UAE2 (Sp; GenBank Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 78 publications
0
33
0
1
Order By: Relevance
“…Previously, in vitro investigations followed by preliminary in vivo studies have successfully identified rhizosphere-competent and endophytic PGPA of various mechanisms in Salicornia (El-Tarabily et al, 2019;Mathew et al, 2020), mangroves (El-Tarabily et al, 2021a;El-Tarabily et al, 2021b), and other plant species (Al Hamad et al, 2021;Alblooshi et al, 2022). An extensive in vitro screening was carried out in the current study to find the suitable salt-tolerant endophytic PGPA strains producing high levels of PGRs (auxins, CKs, GA 3 , and PAs) and possessing ACCD activity.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, in vitro investigations followed by preliminary in vivo studies have successfully identified rhizosphere-competent and endophytic PGPA of various mechanisms in Salicornia (El-Tarabily et al, 2019;Mathew et al, 2020), mangroves (El-Tarabily et al, 2021a;El-Tarabily et al, 2021b), and other plant species (Al Hamad et al, 2021;Alblooshi et al, 2022). An extensive in vitro screening was carried out in the current study to find the suitable salt-tolerant endophytic PGPA strains producing high levels of PGRs (auxins, CKs, GA 3 , and PAs) and possessing ACCD activity.…”
Section: Discussionmentioning
confidence: 97%
“…Plants were kept in the greenhouse for 35 days post-treatment (dpt) for Experiments 1 and 2. Disease severity index was recorded for SDS symptoms at 35 dpt (Experiment 1) and at 15 and 35 dpt (Experiment 2) using a scale of 0-5: 0 = no apparent symptoms, 1 = 1-10% necrotic or white area in leaves or rotting in roots, 2 = 11-25%, 3 = 26-50%, 4 = 51-75%, and 5 = 76-100% (Alblooshi et al, 2022). For disease symptoms/recovery of diseased plants, conidial counts of F. solani were recorded at 35 dpt (Experiment 2).…”
Section: In Vivo Greenhouse Experimentsmentioning
confidence: 99%
“…Integrated disease management (IDM) combining BCAs with fungicides can be another option to reduce the impact of fungicides as well as to effectively manage plant diseases (Saeed et al, 2017b;Kamil et al, 2018;Zapata-Sarmiento et al, 2020). In that sense, actinobacteria have been constantly proposed as possible candidates to replace chemical fungicides (Saeed et al, 2017b;Kamil et al, 2018;Alblooshi et al, 2022); thus the disease management capacity of BCAs heavily relies on uncontrollable environmental conditions (Ons et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations